Quercetin self-assembly nanoparticles with antiviral molecules are effective in inhibiting SARS-CoV-2 pseudovirus infection - Alvizo-Báez, Cynthia Aracely; de Jesús González-Escobedo, Marlon; Terrazas-Armendáriz, Luis Daniel; Uscanga-Palomeque, Ashanti Concepción; Luna-Cruz, Itza Eloisa; Martínez-Ruíz, Amalia Maricela; Ruíz-Robles, Mitchel Abraham; Pérez-Tijerina, Eduardo Gerardo; Tamez-Guerra, Reyes; Rodríguez-Padilla, Cristina; Alcocer-González, Juan Manuel (Frontiers in Nanotechnology, 2025)
Polyphenols have recently attracted considerable interest in the development of nanotechnological antiviral strategies. Among them, quercetin is a natural compound with strong antioxidant activity, exceeding that of vitamins C and E, and notable anti-inflammatory properties in respiratory diseases. In this study, quercetin nanoparticles (QCT-NPs) were synthesized and conjugated with remdesivir, an FDA-approved antiviral drug, or curcumin, a natural molecule with well-documented antiviral effects. The antiviral activity of these conjugates was evaluated through pseudovirus neutralization assays using Vero E6 cells, which provide a reliable model due to their high expression of SARS-CoV-2 receptors. The results demonstrated that QCT-NPs + Rem achieved 72.7% neutralization, while QCT-NPs + Cur reached 79.8% against the alpha variant. Notably, both formulations showed improved activity against the delta variant, with QCT-NPs + Rem achieving 98% neutralization and QCT-NPs + Cur 88%. These findings reveal the significant enhancement of antiviral activity when quercetin nanoparticles are conjugated with either remdesivir or curcumin, compared with the effects of the free molecules. Overall, the study highlights the potential of polyphenol-based nanocarrier systems as promising therapeutic strategies against SARS-CoV-2 variants. Further in vivo validation and clinical studies are warranted to explore their translational applications.